Adubação nitrogenada e fosfatada no desenvolvimeno de mudas de uvaia (Eugenia uvalha) - de Souza, Henrique Antunes [UNESP]; da Silva Gurgel, Rafael Lucas; Teixeira, Glauco Antonio; Cavallari, Ludmilla de Lima [UNESP]; de Arruda Rodrigues, Helen Cristina; Mendonca, Vander (Universidade Federal de Uberlândia (UFU), 2009)
Considering the reduced number of works with fertilization of Eugenia uvalha in national literature and being overcome as base the results of the research with fertilization of other fruitful ones, the present work had as objective to study the effect of nitrogen fertilization and phosphorus, in the culture of the Eugenia uvalha. The work was lead in the Department of Agriculture of the Federal University of Lavras, Lavras - MG, in the first semester of 2005. The experiment was adopted the experimental delineation of randomized blocks in factorial project 4 X 4, with four repetitions and 5 plants for parcel, having been 4 doses of phosphorus: 0 kg m(-3); 2,5 kg m(-3); 5,0 kg m(-3); 10,0 kg m(-3); using itself as seasoning source the triple superphosphate. Already for nitrogen, the applications proceeded from 10 in 10 days had been used 4 doses in covering being, had been carried through 4 applications. The applications consisted of a solution with urea, in the doses: 0; 0,8; 1,6 e 3,2 Kg m(-3), in each application had been added to the polyethylene bags, 20 mL of solution contend the N. had been evaluated the following characteristics: height of the dumb one (cm); root length (cm); leaf number; dry substance of the root and the aerial part (g). For the production of changes of Eugenia uvalha of quality, incorporation to the substratum of up to 1,30 kg m(-3) of P(2)O(5) sends regards to it.

Considerando o reduzido número de trabalhos com adubação de uvaia na literatura nacional e tomando-se como base os resultados das pesquisas com adubação de outras frutíferas, o presente trabalho teve como objetivo estudar o efeito da adubação nitrogenada e fosfatada, na cultura da uvaia. O trabalho foi conduzido no Setor de Fruticultura do Departamento de Agricultura da Universidade Federal de Lavras, Lavras - MG, no primeiro semestre de 2005. O experimento foi instalado em um telado tipo nylon (50% de luminosidade) e foi adotado o delineamento experimental de blocos casualizados em esquema fatorial 4 X 4, com quatro repetições e 5 plantas por parcela, sendo 4 doses de fósforo: 0 Kg m-3; 2,5 Kg m-3; 5,0 Kg m-3; 10,0 Kg m-3; utilizando-se como fonte de adubo o superfosfato simples. Já para nitrogênio, foram utilizadas 4 doses em cobertura sendo as aplicações procedidas de 10 em 10 dias, foram realizadas 4 aplicações. As aplicações consistiam em uma solução com uréia, nas doses: 0 mg dm-3; 800 mg dm-3; 1600 mg dm-3 e 3200 mg dm-3, em cada aplicação foram adicionados aos sacos de polietileno, 20 mL de solução contendo o N. Foram avaliadas as seguintes características: altura da muda (cm); comprimento de raiz (cm); número de folhas; matéria seca da raiz e da parte aérea (g). Para a produção de mudas de uvaia de qualidade, recomenda-se a incorporação ao substrato de até 2,5 Kg m-3 de P2O5.
Fertilization of nitrogen and phosphorus in production of uvaia seedlings
Keywords: Fertilizer; Nutrition; Fruit; Eugenia uvalha